Kinetika Adsorpsi Pada Penjerapan Ion TImbal (Pb+2) Terlarut Dalam Air Menggunakan Partikel Tricalcium Phosphate - Indah Fitriani; Ahmad Fadli; Zultiniar Zultiniar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
One of the heavy metals can pollute the waters is metal ion of Pb2+. Concentration of ions Pb2+ can be removed by adsorption method. The purposes of this research are to observe the effect of stirring rate and concentration on the adsorption of metal ions Pb2+ using adsorbents tricalciumphsphate (TCP) and determine a suitable adsorption kinetics model. Pb2+ solution (2,736 mg / L, 8,546 mg / L and 14,619 mg / L) of 500 mL were added 1 g of TCP in a glass beaker while stirred with variation of rate (100 rpm, 200 rpm and 300 rpm) at a temperature of 30oC. Pb2+ solution was taken at a certain time, then the solution filtered and analyzed by atomic absorption spectrophotometer (AAS). The result showed that rate of adsorption increased with concentration of adsorbat and stirring rate. Minimum constant value of adsorption kinetic was 0,865 g/mg.min obtained at adsorbate concentration of 2,736 mg/L and stirring rate of 100 rpm. Whereas maximum value of adsorption kinetics constant 3.045 g / mg.min obtained at a concentration 14.619 mg / L stirring rate 300 rpm.Key words : Kinetic, Adsorption, Timbale, Tricalcium phosphate